Analisis Eufemisme Pada Berita Utama Surat Kabar Solopos Edisi Bulan Januari 2015 - Nia Irawati, Diyan; , Prof. dr. Markhamah, M.Hum (2016)
This study aims to: (1) identify the form of euphemisms which appeared in the main news section Solopos newspaper in January 2015; and (2) identify the benefits of the use of euphemisms in the news sections of newspapers Solopos January 2015. This type of qualitative research. The object of this study is the use of euphemisms found in newspaper headlines Solopos the January issue of 2015. The results as follows: First, the form of euphemisms are classified into five: (1) the use of abbreviations, (2) use of the word uptake, (3) the use of foreign terms, (4) the use of metaphor, (5) the use perifrasis. From these data it can be seen that the use of other forms of euphemism is the most dominant use of metaphor is by frequency of use 47%. Nearly half of the data found the use of the form is the use of metaphor. Second, the benefits of the use of euphemisms are classified into five: (1) For the courtesy and convenience, (2) To disguise meaning, (3) To reduce shame, (4) To carry out the religious orders. From these data it can be seen that the benefits of using the euphemism of the most dominant in the use of courtesy and comfort factor with the use of a frequency of 42%. Nearly half of the data that was found was the use of the form factor the use of courtesy and comfort.